Membangun Sekolah Ramah Anak: Sosialisasi Dan Edukasi Anti-Perundungan Di Sdn 023 Sungai Geringging - Winario, Mohd; Putra, Aroiyan Faiz; Putri, Alfira Huriyah; Sunelti, Detri; Sarini, Elfi; Jenari, Felisa; Anggiani, Mei Dinda; Afifah, Nur; Miza, Rauzatul; Suhayanti, Suhayanti; Sisda, Tiara Melfia; Rahmayani, Wahyu (EL-EMIR INSTITUTE, 2025)
This community service activity aims to increase the understanding and awareness of students at SDN 023 Sungai Geringging regarding the dangers of bullying, as well as to foster mutual respect and create a child-friendly school environment. The implementation method involved interactive socialization, delivery of anti-bullying educational material using visual media and storytelling, group discussions, and simulations of positive behavior. This approach was chosen to help students more easily grasp the messages conveyed and apply them in their daily lives. Additionally, teachers were involved as supervisors and facilitators to ensure the sustainability of the program at school. The results of the activity showed an increase in students’ knowledge about the forms and impacts of bullying, the emergence of student commitment to refrain from bullying, and the creation of a more harmonious classroom atmosphere. This program is expected to be an initial step toward establishing a safe, comfortable, and bullying-free school culture.